2019
DOI: 10.2495/ut190151
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Predisposition and Behavior Towards Mobility-as-a-Service Among University Students in a Developing Country

Abstract: Mobility-as-a-Service (MaaS) has been recently gaining ground, presenting a shift away from existing ownership-based transportation and towards access-based ones. MaaS is still surrounded by uncertainties: its development and applicability are mainly centered in developed countries; however, we believe that MaaS is modular, adaptable and applicable to several realities. In this sense, this study aims to examine university student's demand and predisposition for MaaS usage in a developing country, as well as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…in this sense, users who own the car but are open to sharing, and those who do not own the car, and use any of the other alternatives, present less harmful measures for urban transport. given the aforementioned and based on the importance of the transport mode choice, presented as the result of a survey with over 300 students (see gandia et al [36]), Figure 4 depicts the higher and lower factor indicated in our results for each mode of transport based in a spectrum indicating the urban mobility issues.…”
Section: Tree #2: Willingness To Use Maas From Users Without Car Ownershipmentioning
confidence: 86%
See 2 more Smart Citations
“…in this sense, users who own the car but are open to sharing, and those who do not own the car, and use any of the other alternatives, present less harmful measures for urban transport. given the aforementioned and based on the importance of the transport mode choice, presented as the result of a survey with over 300 students (see gandia et al [36]), Figure 4 depicts the higher and lower factor indicated in our results for each mode of transport based in a spectrum indicating the urban mobility issues.…”
Section: Tree #2: Willingness To Use Maas From Users Without Car Ownershipmentioning
confidence: 86%
“…on the other hand, (2) users without car ownership are more willingness to use a Maas scheme with (a) higher transport expenses, (b) daily journals with intermediate distances; (c) casual carpooling habits; and also, (d) mostly commute in day shift. gandia et al [36] states that among car users, the commute alternatives that take longer, with less flexibility and availability -even when offered at lower costs -were not appealing. corroborating with this, car users pointed out availability, comfort and safety as the most important characteristics in the choice of car.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from understanding the customers' requirements in choosing MaaS offerings, it is also advantageous to identify the difficulties that customers are facing in using current MaaS offerings. According to previous studies, the three biggest challenges that customers are facing are wait time, price, and safety (Brezovec, Hampl, 2021;Qin, Wang, 2020;Gandia et al, 2019;Gandia et al, 2021).…”
Section: Customer Analysismentioning
confidence: 99%